2021
DOI: 10.1186/s12934-021-01520-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-pathogen infections and Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a chronic neurodegenerative disease associated with the overproduction and accumulation of amyloid-β peptide and hyperphosphorylation of tau proteins in the brain. Despite extensive research on the amyloid-based mechanism of AD pathogenesis, the underlying cause of AD is not fully understood. No disease-modifying therapies currently exist, and numerous clinical trials have failed to demonstrate any benefits. The recent discovery that the amyloid-β peptide has antimicrobial activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 129 publications
(149 reference statements)
1
72
0
Order By: Relevance
“…All in all, persistent HSV-1 infection and reactivation may present as risk factors, which likely interacts with and adds to other risk factors (e.g., age, ApoE4 genotype and other microbial infections) in the development of AD and other hippocampalrelated brain disorders, as reviewed in Wainberg et al (2021) and Vigasova et al (2021). However, there is no evidence of causation in humans yet as HSV-1 reactivation cannot be measured in the living brain, as Mancuso et al (2019) suggested.…”
Section: Discussionmentioning
confidence: 99%
“…All in all, persistent HSV-1 infection and reactivation may present as risk factors, which likely interacts with and adds to other risk factors (e.g., age, ApoE4 genotype and other microbial infections) in the development of AD and other hippocampalrelated brain disorders, as reviewed in Wainberg et al (2021) and Vigasova et al (2021). However, there is no evidence of causation in humans yet as HSV-1 reactivation cannot be measured in the living brain, as Mancuso et al (2019) suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer disease is a chronic neurodegenerative disease associated with the overproduction and accumulation of amyloid‐β peptide and hyperphosphorylation of tau proteins in the brain. Despite extensive research on the amyloid‐based mechanism of Alzheimer disease pathogenesis, its underlying cause is not fully understood 138 . Alzheimer disease patients exhibit neuroinflammation consistent with infection, including microglial activation, inflammasome activation, complement activation, and altered cytokine profiles.…”
Section: The Perio‐systemic Connection: Connected By Viruses or By Ba...mentioning
confidence: 99%
“…Nowadays it is more and more accepted that chronic inflammation provides the base of serious chronic, noninflammatory diseases including cardiovascular, neurodegenerative and bowel diseases, diabetes, arthritis, fibrosis and cancer. In the aetiology of the Alzheimer's disease scientists found links between various pathogens and the development of the disease [51][52][53]. There are data indicating that in lateral sclerosis and in multiple sclerosis bacterial or viral infection can be one of the factors that initiates the disease.…”
Section: Clinical Aspectsmentioning
confidence: 99%